Bending Behavior of Zinc‐Coated Hot Stamping Steels. Issue 10 (29th June 2021) - Hofer, Christina; Stadler, Manfred; Kurz, Thomas; Maier-Kiener, Verena; Mayerhofer, Alexander; Hebesberger, Thomas; Schnitzer, Ronald
Abstract : In the automotive industry, ultrahigh strength steels allow downgauging while, at the same time, passenger safety is increased. To expand the application fields of martensitic steels, which are frequently produced via hot stamping, cathodic corrosion protection is required. To date, zinc‐coated components are mainly processed via the detour of cold forming, but a precooling step to solidify all zinc phases prior to hot stamping shows great potential to overcome this limitation. Therefore, herein, directly quenched 22MnB5 is compared with an adapted alloy (20MnB8) after quenching with a precooling step. Bendability is used to assess the crash performance. In addition to the damage evolution, investigated via interrupted bending tests, a detailed microstructural analysis of the near‐surface region with respect to grain size, decaburization, inclusions, and other second phases is carried out. While 22MnB5 shows a fully martensitic microstructure, individual ferrite grains are observed within the martensitic matrix in the near‐surface region of 20MnB8. Carbon redistribution from ferrite to the surrounding martensite entails large hardness differences between the constituents as determined by nanoindentation, resulting in an earlier onset of strain localization and, therefore, decreased local formability. Abstract : The bending behavior of zinc‐coated martensitic steels produced via two different cooling routes, namely, with and without precooling, is investigated. Precooling leads to the formation of individual ferrite grains within the martensitic matrix in the near‐surface regions. The associated hardness differences entail an earlier onset of strain localization and, therefore, decreased local formability as required for bending.